Strategic Business Development of XYZ Gaming Using SWOT and Business Model Canvas - Susanto, Devina Elysaputri; Hidayati, Aprihatiningrum (Business Review and Case Studies, 2024)
Background: The gaming industry, particularly in Indonesia, continues to grow, offering significant opportunities for business development. Purpose: This research examines the current and future business models of XYZ using SWOT analysis and the Business Model Canvas (BMC) to propose strategies for revenue growth and market expansion. Design/methodology/approach: A qualitative study was conducted, incorporating document analysis, surveys of 35 consumers, and the integration of external (market, customer, competitor, PEST) and internal (HR, marketing, operations, finance) analyses. SWOT analysis results informed the development of an enhanced BMC. Findings/results: The research identified opportunities for XYZ to introduce custom merchandise bundled with services, expand geographic and demographic target markets, and diversify sales channels. The new BMC demonstrates a strategic pivot to include customers aged 13–65 across Indonesia, Australia, and other regions, supported by additional platforms like Shopee and Tokopedia. Conclusion: This study highlights how businesses in the gaming sector can adapt dynamically to external and internal conditions through strategic innovations and comprehensive analyses. Originality/value: By integrating SWOT and BMC with empirical data, this research contributes a state-of-the-art framework for analyzing and innovating business models in the competitive gaming industry.Keywords: SWOT analysis, business model canvas, gaming industry, business development, market expansion